Kids Are Kids! A case study of collaborative ICT acceptance and use - Schaper, Louise; Pervan, Graham (University of Vienna, 2005)
This paper examines acceptance and use of information and communication technologies (ICT) within a small non-profit, community based health care organisation. The study described involved a longitudinal multi-method investigation of technology acceptance and use, collecting quantitative and qualitative data over a 6-month period. The results of this study suggest that traditional models of acceptance may not adequately capture the dynamics of technology acceptance in small non-profit organisations within the health sector. The data illustrates the importance of context, people, organisational and systems issues in the use and acceptance of ICT, and the dynamic interaction which changes over time. The key finding from this research suggests that ICT not only supported collaboration, but that the collaborative nature of the organisation was at the core of the success of the information system implementation. The significance of this work and the theoretical and practical implications of the findings are discussed.